KEANEKARAGAMAN JENIS BURUNG AIR DI KAWASAN EKOWISATA HUTAN BAKAU DESA LAKAWALI KECAMATAN MALILI KABUPATEN LUWU TIMUR - Makkatenni Makkatenni; Husnaeni Husnaeni; Amirullah Amirullah (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2020)
This research discusses the exploration of bird species diversity in the mangrove ecotourism area of Lakawali Village, Malili District, East Luwu Regency. The aim of this research is to explore the diversity of bird species and their distribution in several mangrove and pond ecosystems in Malili District, East Luwu Regency. The research was conducted at four observation stations in the mangrove ecosystem, namely the mangrove ecosystem in Lakawali Pantai Village, Usu Village, Pinrang Malili Village, and PasiPasi Village. The object of this research was the bird species (avifauna) which found at four observation stations in the mangrove ecosystem and aquaculture ponds in Malili District. Data were collected using the IPA method (Index Puncuald'Abondence), observation, and documentation. Data analysis was done by counting the number of bird species from each order found, while the conservation status was determined based on Permen LHK No. P.106/MENLHK/SETJEN/KUM.1/12/2018 and the IUCN’s red list. The results of the research showed that the number of bird species found in mangrove ecosystems and aquaculture ponds around mangroves in the Malili district consisted of 48 species of 13 orders, dominated by Passeriformes and Ciconiiformes. The distribution of the highest number of bird species was found in the KampungPinrangMalili area, followed by Ussu Village, LakawaliPantai Village, and the lowest was in PasiPasi Village. There are two types of birds with NT conservation status (Near Threatened = almost threatened), namely the white belly albatross or Spizaetuscirrhatus (Gmelin, 1788) and the Sulawesi snake eagle or Spilornisrufipectus (Gould, 1858), most of which have the least concern (low risk) LC conservation status and are not protected.